1991
DOI: 10.1128/aac.35.1.130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of subject age on the inhibition of oxidative metabolism by ciprofloxacin

Abstract: Case reports suggest that the magnitude of inhibition of oxidative metabolism produced by ciprofloxacin may be greater in elderly subjects. We examined the effect of oral ciprofloxacin on antipyrine disposition in 13 young (ages, 23 to 34 years) and 9 elderly (ages, 65 to 82 years) healthy volunteers. Ciprofloxacin decreased antipyrine oral clearance in young and elderly subjects (P < 0.05), with the average decreases being similar in both groups (23.3% for the young subjects and 27.9% for the elderly subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Gatifloxacin does not significantly alter the pharmacokinetics of intravenous midazolam [250]. Waite and coworkers demonstrated that elderly subjects are not more sensitive than younger subjects to the inhibitory effect of ciprofloxacin on hepatic metabolism of antipyrine [251]. Similarly, Loi and coworkers demonstrated that elderly subjects are not more sensitive to the inhibitory effect of ciprofloxacin on hepatic metabolism of theophylline [252].…”
Section: Metabolism Interactionsmentioning
confidence: 92%
“…Gatifloxacin does not significantly alter the pharmacokinetics of intravenous midazolam [250]. Waite and coworkers demonstrated that elderly subjects are not more sensitive than younger subjects to the inhibitory effect of ciprofloxacin on hepatic metabolism of antipyrine [251]. Similarly, Loi and coworkers demonstrated that elderly subjects are not more sensitive to the inhibitory effect of ciprofloxacin on hepatic metabolism of theophylline [252].…”
Section: Metabolism Interactionsmentioning
confidence: 92%
“…treatment compared with the administration before ciprofioxacin treatment. No effect of age on the inhibition of antipyrine metabolism by ciprofioxacin was seen (WAITE et al 1991). In contrast, a pronounced inhibitory effect on the hydroxylation of antipyrine was found after a single dose of 400mg enoxacin (BOETTCHER and WOLTER 1989).…”
Section: Antipyrinementioning
confidence: 99%